Latino Pentecostal identity : evangelical faith, self, and society - Sánchez-Walsh, Arlene M. (New York : Columbia University Press, 2003)
-- Benjamin Ortiz, In These Times.
Latinos recently surpassed African Americans as the largest U.S. minority. Of the approximately 37 million Latinos living in the United States, nearly 5 million declare themselves to be either Pentecostal or Charismatic, and more convert every day. Latino Pentecostal Identity examines the rise of Pentecostalism among Latinos and their conversion from other denominations, the difficulties involved in reconciling conflicts of ethnic and religious identity, how evangelical groups encourage the severing of ethnic ties in favor of spiritual community, and the ambivalence Latinos face when their faith fails to protect them from racial discrimination. Drawing upon extensive fieldwork, surveys, and personal interviews, the book also considers issues such as the com-modification of Latino evangelical culture, the Latinization of Pentecostalism, and the ways in which Latino Pentecostals have differentiated themselves from the larger Latino Catholic culture.
List of Illustrations; Preface; Acknowledgments; Introduction; 1. El Aposento Alto; 2. Workers for the Harvest: LABI and the Institutionalizing of a Latino Pentecostal Identity; 3. Normal Church Can't Take Us: Victory Outreach and the Re-Creation of a Latino Pentecostal Identity -- 4. Slipping Into Darkness: God's Anointed Now Generation and the Making of a Latino Evangelical Youth Culture; 5. Worlds Apart: The Vineyard, La Vina, and the American Evangelical Subculture; Epilogue; Appendix; Notes; Bibliography; Index.
Includes bibliographical references (pages 221-229) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Hispanic American Pentecostals; RELIGION -- Messianic Judaism; RELIGION -- General; Hispanic American Pentecostals